A review of the leafhopper tribe Hyalojassini (Hemiptera: Cicadellidae: Iassinae) with description of new taxa - Dai, Wu; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2015)
The morphologically diverse leafhopper tribe Hyalojassini is reinstated from synonymy under Iassini based on distinctive features of the male genitalia and a key to the Oriental genera is given. The previously monotypic genera Hyalojassus Evans and Coriojassus Evans are revised and redescribed based on study of the type species. The following new genera and species are described from Thailand and China and placed in Hyalojassini: Kanchanaburiassus maculatus gen. nov. & sp. nov. from Kanchanaburi, Thailand; Lamelliassus chaingmaiensis gen. & sp. nov. from Chaingmai, Thailand; Siamiassus constanti gen. & sp. nov. from Loei, Thailand ; Decliviassus gen nov. with D. bipunctatus sp. nov., D. maculatus sp. nov., and D. nudus sp. nov., from Thailand; Trocniassus gen. nov. with T. shaanxiensis and T. henanensis sp. nov.; Hyalojassus elongatus sp. nov. and H. punctulatus sp. nov. from Thailand and H. yunnanensis sp. nov. from China; Coriojassus loeiensis sp. nov. from Thailand, C. yunnanensis sp. nov. and C. zhejiangensis sp. nov. from Yunnan and Zhejiang, China, respectively, the latter representing the first records of the genus from China. Sinojassus Dai et al. 2010 (nec Zhang 1985) is a junior homonym, thus a new replacement name, Siniassus nom. nov., is proposed, the genus is transferred to Hyalojassini, and the following new combinations are made: Siniassus loberus (Dai, Zhang & Zhang, 2010), Siniassus aspinus (Dai, Zhang & Zhang, 2010), Siniassus compressus (Dai, Zhang & Zhang, 2010) and Siniassus webbi (Dai & Dietrich, 2010). Detailed morphological descriptions and illustrations for all new taxa are provided. The following New World genera share the diagnostic morphological features of Hyalojassini and are newly placed in this tribe: Absheta Blocker, Aztrania Blocker, Baldriga Blocker, Bertawolia Blocker, Betawala Blocker, Comanopa Blocker, Daveyoungana Blocker & Webb, Derakandra Blocker, Donleva Blocker, Gargaropsis Fowler, Garlica Blocker, Gehundra Blocker, Goblinaja Kramer, Grunchia Kramer, Jivena Blocker, Julipopa Blocker, Maranata Blocker, Mogenola Blocker, Momoria Blocker, Neotrocnada Krishnankutty & Dietrich, Penestragania Beamer & Lawson, Redaprata Blocker, Stragania Stål, Torenadoga Blocker, and Webaskola Blocker.